EUROPEAN UNION’S JUSTIFICATION OF MILITARISATION THROUGH THE CONCEPT OF STRATEGIC PEACE - Popadić, Uroš (Political Review, 2026)
The article examines how the European Union’s post-2022 security approach and discourse redefine the meaning of peace through the emergence of what is conceptualised in the paper as strategic peace. Building on critical peace scholarship, the article argues that strategic peace represents a discursive synthesis of peace and deterrence, in which peace is no longer understood as the opposite of militarization but as something sustained through it. Through a content analysis of major EU strategies and the discourse within them, the article shows how Russia was framed as an existential threat to European stability despite its arguably limited direct military risk, legitimizing increased defense spending, NATO expansion, and thus a further militarization of the EU. This reframing of peace allows EU member states to militarize while maintaining a positive self-image of normative peacefulness, presenting military spending and strategic alignment as peace-preserving. Strategic peace is conceptualized as a broader transformation from liberal, cooperative notions of peace toward a deterrence-based understanding that normalizes militarization as necessary for European peace and security.
Keywords: strategic peace; security discourse; EU militarization; peace and security; European security